Testing the effect of ocular aberrations in the perceived transverse chromatic aberration - Aissati, Sara (Biomed Opt Express, 2020)
We have measured the ocular transverse chromatic aberration (TCA) in 11 subjects using 2D-two-color Vernier alignment, for two pupil diameters, in a polychromatic adaptive optics (AO) system. TCA measurements were performed for two pupil diameters: for a small pupil (2-mm), referred to as ‘optical TCA’ (oTCA), and for a large pupil (6-mm), referred to ‘perceived TCA’ (pTCA). Also, the TCA was measured through both natural aberrations (HOAs) and AO-corrected aberrations. Computer simulations of pTCA incorporated longitudinal chromatic aberration (LCA), the patient’s HOAs measured with Hartmann-Shack, and the Stiles-Crawford effect (SCE), measured objectively by laser ray tracing. The oTCA and the simulated pTCA (no aberrations) were shifted nasally 1.20 arcmin and 1.40 arcmin respectively. The experimental pTCA (-0.27 arcmin horizontally and -0.62 vertically) was well predicted (81%) by simulations when both the individual HOAs and SCE were considered. Both HOAs and SCE interact with oTCA, reducing it in magnitude and changing its orientation. The results indicate that estimations of polychromatic image quality should incorporate patient’s specific data of HOAs, LCA, TCA & SCE.